2017
DOI: 10.1021/acs.organomet.6b00869
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Single-Atom and Small-Domain Platinum via Combining Organometallic Chemisorption and Atomic Layer Deposition

Abstract: Oxide-supported single-atom Pt materials are prepared by combining surface organometallic chemisorption with atomic layer deposition (ALD). Here Pt is supported as a discrete monatomic "pincer" complex, stabilized by an atomic layer deposition (ALD) derived oxide overcoat, and then calcined at 400 °C under O 2 . ALD-derived Al 2 O 3 , TiO 2 , and ZnO overlayers are effective in suppressing Pt sintering and significantly stabilizing single Pt atoms. Furthermore, this procedure decreases the overall Pt nuclearit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 151 publications
(279 reference statements)
0
29
0
Order By: Relevance
“…22 Thus in the eld of heterogeneous catalysis, despite of signicant work performed to understand the single atom catalysts, there exits discrepancy in the literature about the catalytic capabilities of the single atom catalysts, as such some reports show single atoms as the enhanced active centers; [23][24][25][26] while, other reports show that the nanoparticles are the more active species in similar systems. 27,28 In any cases, the common agreement is that the more the dispersed Pt sites, the more adsorption sites for CO, and hence the better CO adsorption properties. However, it alone is not a sufficient condition to facilitate the reaction at low temperature.…”
Section: Introductionmentioning
confidence: 87%
“…22 Thus in the eld of heterogeneous catalysis, despite of signicant work performed to understand the single atom catalysts, there exits discrepancy in the literature about the catalytic capabilities of the single atom catalysts, as such some reports show single atoms as the enhanced active centers; [23][24][25][26] while, other reports show that the nanoparticles are the more active species in similar systems. 27,28 In any cases, the common agreement is that the more the dispersed Pt sites, the more adsorption sites for CO, and hence the better CO adsorption properties. However, it alone is not a sufficient condition to facilitate the reaction at low temperature.…”
Section: Introductionmentioning
confidence: 87%
“…[8] However, it is still a big challenge to synthesize robust SACs with stable, but reactive, metal sites at the atomic scale due to their high surface energies. To achieve atomic dispersion of metal species on carbon-based substrates or metal compounds, various traditional chemical routes, such as: 1) solvent strategy that using solvent dispersion effect, [9][10][11][12][13] 2) carrier modification strategy that designing load sites for anchoring metal atoms, [14] 3) metal-organic molecular strategy that synthesizing metal-organic framework based on isolated metal nodes, [15,16] and 4) additional energy strategy that utilizing external energy for doping of metals as isolated atoms, [17][18][19][20][21][22] have been explored. Among them, the solvent-based procedures, including impregnation/ion-exchange, [9] iced-photochemistry, [10] precursor-dilution strategy, [11] lyophilization, [12] and electrospinning, [13] are universal for producing homogeneous dispersions of different atomic metal species, although they are normally associated with a high waste cost and low yield.…”
Section: Gas Diffusion Strategy For Inserting Atomic Iron Sites Into mentioning
confidence: 99%
“…In contrast, both carrier modification strategy and metalorganic molecular strategy often suffer from tedious substrate modification (e.g., defect engineering) [14] or complicated complex organic synthesis (e.g., porphyrinic triazine-derived frameworks [15] and conjugated metal-organic frameworks [16] ). Moreover, additional energy strategies, including atomic layer deposition, [17] galvanic replacement, [18] microwave, [19] high temperature migration, [20] high temperature shockwave, [21] and metal bulk transformation, [22] are often energy intensive, involving expensive equipment and/or extreme conditions (e.g., high temperature input). Based on this evidence, therefore, it is highly desirable to develop alternative facile routes for introducing nonprecious metal species with a tunable particle size onto carbon substrates to allow for systematically optimizing the electrocatalytic performance.…”
Section: Gas Diffusion Strategy For Inserting Atomic Iron Sites Into mentioning
confidence: 99%
“…9). The IRAS peak for Pt(II) on Al 2 O 3 is known to appear at wavenumbers >2060 cm −1 owing to the isotopic shift 17,32 ; thus it is reasonable to assume that oxidized Pt bears only a slight positive charge (herein, this Pt is referred to as cationic Pt). To further verify this assignment, we analysed Pt 7 /Al 2 O 3 using X-ray photoelectron spectroscopy (XPS), which demonstrated that Pt within the Pt 7 cluster has an oxidation state between Pt(0) and Pt(II) ( Supplementary Fig.…”
Section: Model Structures Of Pt Clusters On Al 2 O 3 and Tio 2 Substrmentioning
confidence: 99%